The Sensitization of Melatonin in Osteosarcoma Cells by Suppression of Anti-Apoptotic Proteins - Seyed Mostafa Mir; Bahman Yousefi; Abdoljalal Marjani; Mahdi Rahimi; Durdi Qujeq (Tabriz University of Medical Sciences, 2020)
Background: Investigation of anti-cancer agents with desirable selective toxicity is critical for cancer therapy. The use of natural adjuvants can be a promising option in reducing the toxicity of the anti-cancer agent. The aim of this study was to investigate the potential application of melatonin (MLT) as a natural adjuvant molecule along with doxorubicin (DOX) to induce cytotoxicity in osteosarcoma (OS) cells. Methods: Human OS cell lines included Saos-2, MG-63, and Human Bone Marrow Mesenchymal Stem Cells (hBM-MSCs) were treated with free DOX, free MLT, DOX-loaded NPs (DOX-NPs), MLT-loaded NPs (MLT-NPs), combination of DOX and MLT (DOX-MLT) and combination of DOX and MLT-loaded NPs (DOX-MLT-NPs) in separated cell culture. Cell proliferation of experiments were evaluated by MTT assay after 24 h. Total protein levels were determined by enzyme immunoassay ELISA.Results: Herein, we found the combination of MLT with DOX, especially formulated in nano-form, is resulted in a significant reduction in the protein levels of both X-linked Inhibitor of Apoptosis (XIAP) and Survivin (p<0.0001). Indeed, there was a significant decrease in the expression of XIAP and Survivin when MLT is combined with DOX compared to the individual treatments.Conclusion: Our findings indicated the synergism of the antitumor effect could be due to the down-regulation of XIAP and Survivin in the levels of protein.